Uncovering phenotypes of poor-pitch singing: the Sung Performance Battery (SPB) - Berkowska, Magdalena; Dalla Bella, Simone (Frontiers in Psychology, 2013)
Singing is as natural as speaking for humans. Increasing evidence shows that the layman can carry a tune (e.g., when asked to sing a well-known song or to imitate single pitches, intervals and short melodies). Yet, important individual differences exist in the general population with regard to singing proficiency. Some individuals are particularly inaccurate or imprecise in producing or imitating pitch information (poor-pitch singers), thus showing a variety of singing phenotypes. Unfortunately, so far there is not a standard set of tasks for assessing singing proficiency in the general population, allowing to uncover and characterize individual profiles of poor-pitch singing. Different tasks and analysis methods are typically used in various experiments, making the comparison of the results across studies arduous. To fill this gap we propose here a new tool for assessing singing proficiency (the Sung Performance Battery, SPB). The SPB starts from the assessment of participants’ vocal range followed by five tasks: 1) single-pitch matching, 2) pitch-interval matching, 3) novel-melody matching, 4) singing from memory of familiar melodies (with lyrics and on a syllable), and 5) singing of familiar melodies (with lyrics and on a syllable) at a slow tempo indicated by a metronome. Data analysis via acoustical methods provides objective measures of pitch accuracy and precision in terms of absolute and relative pitch. The SPB has been tested in a group of 50 occasional singers. The results indicate that the battery is useful for characterizing proficient singing and for detecting cases of inaccurate and/or imprecise singing.